A direct parallel implementation of the Hoshen–Kopelman algorithm for distributed memory architectures - Teuler, J.M.; Gimel, J.C. (Computer physics communications, 2000)
We present a direct (i.e. non iterative) method for identifying the clusters of a cubic lattice on a distributed memory parallel machine. We describe the various cluster properties which we were able to compute with this method. Finally, we give some performance measurements.